2016
DOI: 10.1210/jc.2015-3874
|View full text |Cite
|
Sign up to set email alerts
|

The p.Leu167del Mutation in APOE Gene Causes Autosomal Dominant Hypercholesterolemia by Down-regulation of LDL Receptor Expression in Hepatocytes

Abstract: p.Leu167del mutation in APOE gene is the cause of hypercholesterolemia in the 3.1% of our ADH subjects without LDLR, APOB, and PCSK9 mutations. The mechanism by which this mutation is associated to ADH is that VLDL carrying the mutant apo E produces LDLR down-regulation, thereby raising plasma low-density lipoprotein cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 33 publications
(29 reference statements)
3
51
0
Order By: Relevance
“…Additional mechanisms include mutations affecting the apolipoprotein B ([ApoB], the key structural component of LDLs and very low‐density lipoproteins [VLDLs]), and the gene of pro‐protein convertase subtilisin‐kexin type 9 (PCSK9), which promotes the LDLR internalization and destruction in hepatocytes (Benn, Watts, Tybjærg‐Hansen, & Nordestgaard, ; Raal et al, ). Other rare forms of FH are due to mutation in the apolipoprotein E (ApoE) gene (Wiegman et al, ) and LDL receptor adaptor protein 1 (LDLRAP1), which encodes a protein required for clathrin‐mediated internalization of the LDLR (Cenarro et al, ). Nevertheless, in about 60% of patients the underlying mutation remains unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…Additional mechanisms include mutations affecting the apolipoprotein B ([ApoB], the key structural component of LDLs and very low‐density lipoproteins [VLDLs]), and the gene of pro‐protein convertase subtilisin‐kexin type 9 (PCSK9), which promotes the LDLR internalization and destruction in hepatocytes (Benn, Watts, Tybjærg‐Hansen, & Nordestgaard, ; Raal et al, ). Other rare forms of FH are due to mutation in the apolipoprotein E (ApoE) gene (Wiegman et al, ) and LDL receptor adaptor protein 1 (LDLRAP1), which encodes a protein required for clathrin‐mediated internalization of the LDLR (Cenarro et al, ). Nevertheless, in about 60% of patients the underlying mutation remains unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous familial hypercholesterolemia (HeFH), the most frequent monogenic disorder of human metabolism caused by some mutations in the genes that encode for the low-density lipoprotein (LDL) receptor, apolipoprotein (apo) B, proprotein convertase subtilisin/kexin-type 9 (PCSK9) or apo E 1, 2 , entails an increased risk of premature cardiovascular disease 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We found only one patient heterozygous for a known apoE variant [p.(Leu167del)], considered the cause of FH with dominant transmission [3]. Recently a large study conducted in 228 Spanish FH patients in whom the LDLR, APOB and PCSK9 pathogenic variants had been excluded, showed that nine patients (3.1%) were carriers of the p.(Leu167del) variant [20]. This variant was found to segregate with FH phenotype among index cases' family members.…”
Section: Discussionmentioning
confidence: 92%